Pengembangan Media Pembelajaran Matematika “Going To Winner” Berbasis Game di Kelas I Sekolah Dasar - Putri Durrotul Hikmah; Rosiana Mufliva (Jurnal Didaktika Pendidikan Dasar, 2025)
This study is motivated by the low interest of students, particularly in mathematics, specially in addition and subtraction topics for first-grade elementary students. It was found that teachers often have limited variation in teaching approach, relying on monotonous methods and insufficiently utilizing instructional media. This research aims to develop game-based learning media to address the lack of interest and motivation among students, offering a more enjoyable and interactive learning approach. The study employs a Design and Development (D&D) approach using the ADDIE model, which includes the phases of Analysis, Design, Development, Implementation, and Evaluation. The result indicate that the media is highly suitable for use, with an expert assessment score of 97.22% categorized as very feasible, media variation by experts receiving 91.67% also in the very feasible category, and a highly positive validation from teaching practitioners with a score of 100% in the very feasible category. The student evaluation test also showed positive outcomes, with a validation score of 96.10%, while instructional material validation by subject matter experts received a score of 98.48%, categorized as very feasible. The “Gong to Winner” learning media, designed and tested on students, demonstrated positive responses in terms of motivation, ease of use, and educational benefits.